EMPLOYEE ACHIEVEMENT IMPACT: PLACEMENT, COMPETENCY, AND MOTIVATION AS INTERVENING VARIABLES - Sukardi, Sukardi; Aryanti, Wiwin; Djumarno, Djumarno; Herminingsih, Anik; Kasmir, Kasmir (Universitas Brawijaya, Indonesia, 2021)
The purpose of this study was to determine the effect of placement and competence on work performance of permanent employees. Mediated by motivation in the welding section of the Automotive Industry in Tambun Bekasi. The research method used quantitative with a population of 125 employees. The number of samples used was 125 permanent employees in the Automotive Industry welding section in Tambun Bekasi. The sampling technique used was nonprobability sampling and the sampling method was saturated sampling. Then the analysis test was carried out using Structural Equation Modeling (SEM) and processed with the LISREL version 8.8 application. The results of this study indicate that placement and competence have a direct significant effect on work performance, while placement and competence through the intervening motivation variable have an effect on work performance, while motivation as an intervening variable has a significant effect on work performance. Subsequent research can be developed by adding variables of job design and physical conditions of work.